DAMPAK PERCERAIAN PADA PERKEMBANGAN SOSIAL DAN EMOSIONAL ANAK USIA 5-6 TAHUN - Reski Yulina Widiastuti (PG-PAUD Trunojoyo, 2015)
Impact Of Divorce On Social And Emotional Development Of Children Aged 5-6 Years. This research aims to: (1) Describe the problem causes by the divorce of  their parent, (2) Describe the care that is applied parents after divorce, (3) Describe the social and emotional development of children after divorce (4) Describe the role of parents in the home, (5) Describe the role of kindergarten teacher in school. The subjects of the study are children aged 5-6 years, amounting to 3 people. This study is a qualitative research case based. Analysis of the data used that model of Miles and Huberman which consists of data reduction, data display, and verification. Data collection techniques are observation, interviews, and documentation. The results showed that: (1) Divorce of parents due to economic problems, differences in social status, did not get the blessing from their parents, infidelity, domestic violence, and married too early, (2) post-divorce child care assisted by a close relative or a maid when the parents went to work, (3) social and emotional development of children showed more positive development than social and emotional development is negative, (4) The role of parents with sufficient physical and psychological needs of children, to give understanding, in cooperation with the parenting, consult with experts, to train children to share their stories, provide the necessary information to the teacher, and also follow up on all the things that kids do in school, (5) the role of teachers by doing approach, advising, reward the positive attitude shown every child, giving duties in accordance with the child's ability, are invited to be active in every activity, gives an interesting, maintaining the psychological condition of children, and to share the information to the people parents.